Why It Is Essential to Teach About Mental Health Issues in Criminal Law (And a Primer on How To Do It) - Richard E. Redding (Washington University Journal of Law & Policy, 2004)
Forensic mental health issues should be an integral part of the criminal law curriculum, beginning with the first-year criminal law course. This Essay presents recommendations for teaching mental health issues in first-year criminal law, presents empirical data indicating that first-year students have mixed, though generally positive, reactions to incorporating such non-traditional content into the course, and provides a syllabus for an upper-level course in criminal law and psychology. Incorporating mental health topics into the traditional criminal law curriculum is part of the ongoing trend in legal education towards expanding pedagogy beyond legal doctrine into relevant social science disciplines that can inform legal policy and students’ understanding of the criminal justice system, perhaps more so than many of the doctrinal lessons we now teach.
Keywords: Mental health; Law schools -- Curricula; Criminal law